Studi Rasionalitas Penggunaan Antibiotika di RSUD DR. Murjani Sampit - darini kurniawati (Jurnal Pelayanan Kefarmasian dan Sains, 2021)
Background Antibiotics are the most widely used type of drug due to the high incidence of infection in Indonesia. From the results of the preliminary study for 3 days prospectively, as many as 44 patients who received treatment, 37 patients (87%) received antibiotic therapy. There is the use of expensive antibiotics from the 3rd generation cephalosporin group, there are 4 trade names, 2 generation cephalosporins and 1 there are 6 trade names. Expensive sulbenicin and aminoglycoside derivatives are also found, Gentamicin and Kanamycin. The relatively cheap antibiotics are chloramphenicol, tetracycline, cotrimoxazole, but various brands of these products are popular with "me too drug" being used, of course with varying prices. Government Hospital type C should refer to the use of generic drugs and refer to the national antibiotic use guidelines. Therefore, researchers want to investigate further. Objective To study the patterns of antibiotic use at the Dr Murjani Sampit Regional Hospital before and after the Educational Information Communication on Guidelines for the Use of National Antibiotics. Method This study used a retospective and prospective descriptive observational study with pre-research intervention to medical personnel on the Guidelines for the Use of National Antibiotics and Rational Pharmacotherapy, to paramedics on the stability and method of administering injection dosage antibiotics. This retrospective study used medical documents for patients at 3 months intervals from inpatients for Surgery, Internal Medicine, Children and Gynecology. Prospective study of inpatients at the UPF Surgery, Internal Medicine, Children, and Gynecology for 1 week. Analysis of antibiotic prescribing patterns and the rationality of using antibiotics based on the National Antibiotic Guidelines and Use references. Results The distribution pattern of antibiotic use from a retrospective study of 447 patients, there were 260 (58.1%) patients using antibiotics. Even in obstetrics UPF, 100% of the gynecologists used antibiotics. The results of a retrospective study on the rational category and the cost of using antibiotics found the rationality of the indications and patients only reached <50% of the 4 UPFs studied. The rationality of the dosage regimen was <20% and the dose regimen <10%. Average cost of antibiotics wasted Rp. 80,374 per patient. The highest wastage was at UPF Obstetrics and Gynecology of Rp. 145,223/patient, while the lowest was in UPF Children of Rp. 40,837,-/ patient. From the prospective study, there were 260 patients, 100% used antibiotics with the rationality of the indications and the patients <50%, the rationality of the drug selection was <20%, the rationality of the dosage regimen was <10%. The average wasted cost of antibiotics which became a burden for patients was Rp. 74,793,-/patient with the highest waste at the UPF Gynecology Rp. 119,272,-/patient and the lowest in UPF Children was Rp. 34,697,-/patient. Conclusion The pattern of antibiotic use in Dr Murjani Sampit Hospital in the 4 UPFs studied was 49.1 - 100%. There was an irrational use of antibiotics, the right indication was <43%, the right drug selection was <37.7%, the right dose regimen was <20.8%, there was a combination of antibiotic interactions <6.9% and there was a waste from the use of antibiotics Rp. 80,374,-/patient in retrospective and Rp. 74,793,-/patient in the prospective study. Keywords Rationality, Antibiotics